Effect of microstructure on corrosion and wear behavior of laser-clad CoCrFeMo0.85Ni compositionally complex alloy coatings - Oppong, Gifty B.; Fanicchia, Francesco; Geambazu, Laura E.; Paul, Shiladitya; Barras, Josh; Davison, Emily; Csaki, Ioana; Karlsdóttir, Sigrún N. (Elsevier, 2026)
Laser-clad CoCrFeMo0.85Ni compositionally complex alloy (CCA) coatings were fabricated from gas atomized (GA) and mechanically alloyed (MA) powders, forming dense, adherent multilayer structures of FCC, BCC, and intermetallic σ-phases. The MA resulted in a more heterogeneous multiphase microstructure and lower hardness. Both coatings exhibited localized pitting corrosion. The GA produced a more chemically uniform FCC-based microstructure with spatially segregated σ-phase, reducing local electrochemical driving forces for micro-galvanic corrosion and pit initiation, although localized breakdown persisted once passivity was lost. Wear performance in both coatings was governed by abrasive and adhesive mechanisms facilitated by oxide formation, with maximum wear depth below 10% of the coating thickness.
Keywords: Compositionally Complex Alloy; High-Entropy Alloy; Laser Cladding; Corrosion Resistance; Wear Behavior; Mechanical Alloying; Gas Atomization; 4014 Manufacturing Engineering; 40 Engineering; 3403 Macromolecular and materials chemistry; 4016 Materials engineering; 4018 Nanotechnology